Analysis of the needs of teachers of SMAN 3 Sidoardjo in the creation and use of learning media - Nenohai, Jacky Anggara; Rokhim, Deni Ainur; Minata, Zelen Surya; Agustina, Nur Indah; Islamiyah, Kafita Krisnatul; Ronggopuro, Burhanuddin; Habiddin, Habiddin; Peni, Ristiwi; Wahyudi, Bambang; Wahyudi, Asnan (Jurnal Inovasi Teknologi Pendidikan, 2023)
This study aims to analyze the needs of teachers of SMAN 3 Sidoardjo in the creation and use of learning media in the teaching and learning process. The research method used is descriptive qualitative by taking data through a Google form-based questionnaire filled out online. The subjects of the study were 51 teachers of SMAN 3 Sidoardjo. The results of the survey based on questionnaire data obtained showed that the learning media used by the teachers of SMAN 3 Sidoardjo in the teaching process was made by as much as 72.5% and 27.5% were not made by themselves, so the media was obtained from Youtube, Google, and colleagues. The media created by several teachers has obstacles, namely mastery of IT (editing and programming languages), a long time in the development process, and its use has not adjusted to the characteristics of students and unites several media and materials in one platform such as  Learning Management System. Therefore, teachers need training and direct assistance in making intensive and simple learning media without using programming languages, flexible time, and accessible anywhere and anytime. Website-based media to accommodate all the material and learning resources taught so that students can easily use the press and improve their understanding of the material and the quality of learning So that teachers and students can adjust the scope and face problems in the learning process by the demands of the times.